Money Wise Helping Children Learn To Manage Money - Walker, Doris K. (My University, 1993)
This publication teaches competency in money management. It provides an opportunity for children to learn about money management as they grow up.
C731_1993_02
Keywords: C731; Home and Family; Economics; youth development; C